Laser transmission welding of polymers – A review on welding parameters, quality attributes, process monitoring, and applications. (April 2021) - Acherjee, Bappa
Highlights: A comprehensive review on several aspects of the laser transmission welding process is presented. Laser transmission welding parameters and their effects on the performance of the welds are discussed. Laser transmission weld quality attributes used to assess the quality of the welded joints are reviewed. Process monitoring techniques for the laser transmission welding process are discussed. Several applications of laser transmission welding in different industrial sectors have been identified. Abstract: Laser transmission welding (LTW) is nowadays a well-received polymer joining process. New applications are emerging more and more due to the unique advantages of LTW over conventional joining processes. This paper provides a comprehensive review on various aspects of LTW techniques through a detailed survey of several scholarly publications, industrial studies, scientific reports, etc. This review focuses primarily on five major aspects of LTW, which are (a) welding parameters and their effects, (b) weld quality attributes, (c) process monitoring techniques, (d) material combinations, and (e) industrial applications. After an introduction to the process, the welding parameters, and how they influence the LTW process are described first. This is followed by a description of the quality attributes of LTW, including weld strength, weld pool dimensions, part gap-bridging ability, meltdown, and weld morphology. Several process monitoring techniques applied to LTW are then discussed for pre-, post-, and real-time monitoring of the process. Subsequently, material combinations that are successfully welded using LTW are described, including welding of polymer to polymer, metal, ceramic, glass, wood, etc. Finally, several applications of LTW in different industrial sectors are identified, and the results of the review are concluded.